PREPARAÇÃO E CARACTERIZAÇÃO DE FILMES LbL DE FTALOCIANINA DE NÍQUEL E POLIELETRÓLITO SILSESQUIOXANO - Santos, Cleverson Siqueira (2012)
The research focused on the development of electrochemical sensors based on LBL films have grown exponentially in recent years. In this context, this paper reports the development of an electrochemical sensor using the Layer-by-layer (LbL) technique, which enables the construction of ultrathin films from electrostatic interactions between oppositely charged polyelectrolytes. For this purpose, the tetrasulfonated nickel phthalocyanine (NiTsPc) was used as polyanion molecule and the 3-n-propilpyridinium silsesquioxane chloride (SiPy+Cl-) as the polycation. This silsesquioxane polyelectrolyte is an excellent ion exchange and has high ability to form stable films on the surface of solid substrates. The LbL films were built using two different architectures: one with an outer layer of phthalocyanine designated as (SiPy+Cl-/NiTsPc)n and another with the phthalocyanine as the inner layer, (NiTsPc/SiPy+Cl-)n with different bilayers, (where n = number of bilayers). The deposition of the bilayers was monitored using the UV-VIS spectroscopy in the region from 500 to 800 nm, where the phthalocyanines exhibit two absorption bands, one related to the dimeric species at 630 nm and another at 669 nm related to monomeric form. It was observed that the parameters:immersion time, pH and concentration directly influenced the construction of these films and therefore they were optimized. The optimized parameters were: immersion time of 280 s, pH = 8 and concentrations of polyeletrolytes solutions of 2 mg mL-1, which provided stable and homogeneous films, with higher concentrations of monomeric species. Monitoring the bilayers deposition in the UV-VIS region, a linear relationship was obtained between the absorbance and the number of bilayers deposited. FTIR and Raman spectra showed that the interactions between the polyelectrolytes occurs by the SO3 groups in the structure of tetrasulfonated phthalocyanines with the pyridinium groups present in the structure of the SiPy+Cl-. Using the AFM technique, it was observed that the average roughness of the films decreased with the increase of bilayers. On the other hand, the thickness of the films increased with the number of bilayers, and the average thickness of each bilayer was 22 nm for the architecture (SiPy+Cl-/NiTsPc)n, and 19.2 nm for the opposite configuration. The electrodes were applied for simultaneous determination of dopamine (DA) in the presence of the interfering species, such as ascorbic acid (AA) and uric (UA). It was observed that the architecture as well as the thickness of the films has influenced significantly the electrochemical response in the presence of analytes. The film with the highest current density and less positive potential values for these analytes was (SiPy+Cl-/NiTsPc)2. For this electrode, f om the cyclic voltammetry technique, anodic peaks were observed at 0.30 V,0.68 V and 0.74 V in the presence of DA, AA and UA, respectively. Studies in different scan rates in presence of dopamine showed that the kinetics of electron transfer is controlled by diffusion of species to the electrode surface. Using the square wave voltammetry, DA was detected in presence of AA with a peak separation potential of 350 mV. However, for a fixed concentration of DA, it was observed an increase of the intensity of peak current with increasing of AA concentration, which is an indication that the AA electrocatalyzes the oxidation reaction of DA to dopaminequinone, causing an increase in the current, which prevents the accurate determination of these analytes simultaneously. On the other hand, in the presence of UA in a fixed concentration of 4.7 x 10-4 mol L-1, it was possible to quantify DA in the range of 1.0 x 10-5 to 9.9 x 10-5 mol L-1 with a detection limit of 2.37 x 10-6 mol L-1 and quantification limit of 7.9 x 10-6 mol L-1 with peak separation Ep= 500 mV. By varying both the concentration of DA and UA, in the range of 1.0 x 10-4 to 9.0 x 10-4 mol L-1 for DA and 1.0 x 10-5 to 9.9 x 10-5 mol L-1 for UA, it was obtained a correlation coefficient of R = 0.997 and R = 0.988 for AU and DA respectively. The results showed that the electrode (SiPy+Cl-/NiTsPc)2 is selective and sensitive for DA determination in presence of interfering species AA and UA.